Redefining Masculinity in a Web-Based Peer Support Program for Husbands of Women With Gynecologic or Breast Cancers in Nigeria. - Nwozichi, Chinomso; Oshodi-Bakare, Mosidat; Animashaun, Olaide Faosat; Kolawole, Oluwabusola; Martins-Akinlose, Oluwaseun Deborah; Salako, Omolabake Fathiat (Clinical Journal of Oncology Nursing, 2026)
BACKGROUND: Diagnoses of gynecologic and breast cancers in women may impose emotional and psychological burdens on their partners. Traditional notions of masculinity in Nigeria often discourage men from expressing vulnerability or seeking emotional support. This article explores the impact of a web-based peer support program on redefining masculinity among male partners of women diagnosed with these cancers. OBJECTIVES: The study assesses how digital peer support groups facilitate emotional expression, reduce isolation, and promote a redefined, supportive masculinity that embraces empathy, vulnerability, and active caregiving. METHODS: An eight-week web-based peer support intervention was implemented for partners of women with gynecologic and breast cancers. Researchers collected data via semi-structured interviews with 21 male participants and analyzed the data using thematic analysis FINDINGS: Participants reported significant shifts in perceptions of masculinity, embracing emotional vulnerability, improving communication with their spouses, navigating changes in intimacy, and adapting caregiving roles. The digital environment provided anonymity, reducing stigma and fostering open dialogue.